2008
DOI: 10.1177/1089253208328668
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal Echocardiography and Noncardiac Surgery

Abstract: The use of transesophageal echocardiography (TEE) for monitoring during cardiac and noncardiac surgery has increased exponentially over the past few decades. TEE has evolved from a diagnostic tool to a monitoring device and a procedural adjunct. The close proximity of the TEE transducer to the heart generates high-quality images of the intracardiac structures and their spatial orientation. The use of TEE in noncardiac and critical care settings is not well studied, and the evidence of the benefits of its use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 229 publications
(221 reference statements)
0
26
0
1
Order By: Relevance
“…An additional prospective outcome study, found that asymptomatic patients with mild to moderate aortic stenosis had an event-free survival defined as death or aortic valve surgery of 95±2, 75±3, and 60 ±5% at 1, 3, and 5 years and concluded that outcome is worse in this population than previous data has suggested [11]. The identification of severe valvular heart disease contributing to cardiac arrest represents an additional diagnositic consideration that cannot be overlooked Perioperative transesophageal echocardiography has broadened its application beyond the cardiac surgical population, with mounting evidence of benefit to patients undergoing noncardiac surgery [6]. Specifically, TEE may be useful in diagnosing and managing patients with cardiovascular collapse, hypovolemia, coronary ischemia, pericardial diseases, and complex valvular heart disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…An additional prospective outcome study, found that asymptomatic patients with mild to moderate aortic stenosis had an event-free survival defined as death or aortic valve surgery of 95±2, 75±3, and 60 ±5% at 1, 3, and 5 years and concluded that outcome is worse in this population than previous data has suggested [11]. The identification of severe valvular heart disease contributing to cardiac arrest represents an additional diagnositic consideration that cannot be overlooked Perioperative transesophageal echocardiography has broadened its application beyond the cardiac surgical population, with mounting evidence of benefit to patients undergoing noncardiac surgery [6]. Specifically, TEE may be useful in diagnosing and managing patients with cardiovascular collapse, hypovolemia, coronary ischemia, pericardial diseases, and complex valvular heart disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…La primera onda E (early) corresponde al llene temprano del VI y la onda A (auricular) corresponde a la sístole auricular. También se ha visto que la disfunción diastólica se asocia con un mayor número de eventos hemodinámicos postoperatorios, como hipotensión e hipertensión [11][12][13][14][15][16][17] . La Ecocardiografía también permite calcular el gasto cardíaco (GC), parámetro reconocido como un muy buen índi-ce de función cardíaca global y predictor de complicaciones perioperatorias.…”
Section: Ecocardiografía Transesofágica (Ete) Durante Cirugía No Cardunclassified
“…TEE can also assist in the donor selection process [10]. During single sequential lung transplantation, TEE is used as a hemodynamic monitor to assess the effects of one-lung ventilation and pulmonary artery clamping as well as guide the need for extracorporeal support post transplantation [11 • ].…”
Section: Tee In Thoracic Transplantation Surgerymentioning
confidence: 99%